2019
DOI: 10.17265/2328-2169/2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Poor Tourism: Critical Perspective and Implications for Future Research

Abstract: Tourism is viewed as a medium to reduce poverty. The pro-poor tourism (PPT) approach has therefore emerged as the medium for tourism development to influence poverty reduction. The approach stresses on tourism development in ways to accrue net benefits to the poor through diverse strategies including those that generate employment opportunities, infrastructural development, and skills enhancement of locals in entrepreneurial activities. Also stressed is the inclusion of the poor in tourism decision making. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…These results are also consistent with the findings of recent research conducted by the KZN Department of Health, which showed that the status of economically employed persons in the UKDM stood at 41.4%, compared to the provincial rate of 57.7% (UMkhanyakude District Health Plan, 2018-2019. This paper showed that despite the severe constraints on financial resources, efforts have been made to empower local communities so that they can participate in and contribute to their own development through ecotourism projects.…”
Section: Figuresupporting
confidence: 91%
“…These results are also consistent with the findings of recent research conducted by the KZN Department of Health, which showed that the status of economically employed persons in the UKDM stood at 41.4%, compared to the provincial rate of 57.7% (UMkhanyakude District Health Plan, 2018-2019. This paper showed that despite the severe constraints on financial resources, efforts have been made to empower local communities so that they can participate in and contribute to their own development through ecotourism projects.…”
Section: Figuresupporting
confidence: 91%
“…Another result from his study in the SUDENE area of Brazil that government intervention employment in the tourism sector increase around 30 percent compared without government intervention. Akrong (2019) explain that the tourism sector can play important role in socio-economic development.…”
Section: Introductionmentioning
confidence: 99%